Incremental information content of required disclosures contained in... - Bryan, Stephen H. (The Accounting Review, 1997)
This paper analyzes seven mandated disclosures contained in Management Discussion and Analysis (MD&A) to assess their information content. Generally, the results show that certain MD&A disclosures, particularly the discussions of future operations and planned capital expenditures, are associated with future (short-term) performance measures and investment decisions, after control- ling for information contained in financial-statement-based ratios. However, the associations with longer-term results are generally not significant. The study illustrates that, in conjunction with the financial statements, the MD&A disclosures, especially prospective disclosures, can assist in assessing firms' future (short-term) prospects.